Investigating the relationship between social support and quality of life in the elderly - Moghadam, Kamele (J Educ Health Promot, 2020)
BACKGROUND: Dynamic aging depends on providing opportunities to improve the quality of life of the elderly. The objective of this study was to investigate the relationship between social support and quality of life in the elderly in Guilan. MATERIALS AND METHODS: This descriptive-correlational study was conducted in the elderly who visited urban public places in the East of Guilan (mosques, parks, weekly markets, and clubs). A total of 168 elderly who met the inclusion criteria were selected through two-stage, cluster, and convenience sampling. Data were collected using Phillips Standard 23-item social support scale and 12-item quality of life scale-short form. Data were analyzed through descriptive and inferential statistics (Pearson correlation coefficient). RESULTS: The mean score of social support in the elderly in Guilan was 73.25 ± 9.18 and the mean quality of life was obtained at 24.67 ± 7.06. Data analysis showed that there was a significant and positive correlation between social support and quality of life (r = 0.29, P < 0.0001). CONCLUSIONS: Increased social support leads to a higher quality of life in the elderly. Thus, it is necessary to timely identify the needs and promote comprehensive social support to improve the quality of life in the elderly.